Presence of IgG antibodies is not a reliable marker of Toxoplasma gondii infection in feral mice - Lignereux, Louis (2023)
The single-celled parasite Toxoplasma gondii uses mice as a vector to reach its definitive host, the cat, where it can accomplish its sexual reproduction and produce oocysts, which will contaminate the environment. In this study, we have captured 103 feral house mice (Mus musculus) on Kangaroo Island, Australia. We have measured the level of exposure to T.gondii serologically with the Modified Agglutination Test and conjointly with a T.gondii B1 gene PCR. We have included stringent quality control steps in the molecular analysis to reduce the risk of false positivity and false negativity. Our results indicated a low seroprevalence of 0.97%, 95%CI [-0.36; 0.58] associated with the detection of T.gondii genetic material in 51.46%, 95%CI [41.93, 60.88] of mice brains. Neither sex nor mice body weight had an effect on the PCR outcome. We postulate that both the transmission route, horizontal or vertical, and natural selection processes could lead to this discordance which has been observed elsewhere in wild mice. The question of the biological mechanisms allowing the chronic infection of wild mice in the absence of a measurable humoral immune response remains. Our findings indicate that serological studies should not be used to measure the level of exposure to T.gondii in feral house mice.